Whole Genome Comparison of Thermus sp. NMX2.A1 Reveals Principal Carbon Metabolism Differences with Closest Relation Thermus scotoductus SA-01. Issue 9 (1st September 2016) - Müller, Walter J; Tlalajoe, Nokuthula; Cason, Errol D; Litthauer, Derek; Reva, Oleg; Brzuszkiewicz, Elzbieta; van Heerden, Esta
Abstract: Genome sequencing of the yellow-pigmented, thermophilic bacterium Thermus sp. NMX2.A1 resulted in a 2.29 Mb draft genome that encodes for 2312 proteins. The genetic relationship between various strains from the genus Thermus was assessed based on phylogenomic analyses using a concatenated set of conserved proteins. The resulting phylogenetic tree illustrated that Thermus sp. NMX2 A.1 clusters together with Thermus scotoductus SA-01, despite being isolated from vastly different geographical locations. The close evolutionary relationship and metabolic parallels between the two strains has previously been recognized; however, neither strain's genome data were available at that point in time. Genomic comparison of the Thermus sp. NMX2.A1 and T. scotoductus SA-01, as well as other closely related Thermus strains, revealed a high degree of synteny at both the genomic and proteomic level, with processes such as denitrification and natural cell competence appearing to be conserved. However, despite this high level of similarity, analysis revealed a complete, putative Calvin–Benson–Bassham (CBB) cycle in NMX2.A1 that is absent in SA-01. Analysis of horizontally transferred gene islands provide evidence that NMX2 selected these genes due to pressure from its HCO3 - rich environment, which is in stark contrast to that of the deep subsurface isolated SA-01.